2020
DOI: 10.1051/0004-6361/201936792
|View full text |Cite
|
Sign up to set email alerts
|

H II regions and high-mass starless clump candidates

Abstract: Context. The role of ionization feedback on high-mass (> 8 M ) star formation is still highly debated. Questions remain concerning the presence of nearby H ii regions changes the properties of early high-mass star formation and whether H ii regions promote or inhibit the formation of high-mass stars. Aims. To characterize the role of H ii regions on the formation of high-mass stars, we study the properties of a sample of candidates high-mass starless clumps (HMSCs), of which about 90% have masses larger than 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 130 publications
(167 reference statements)
2
11
0
Order By: Relevance
“…15 shows that in the inner Galaxy this threshold falls well inside the region of the pre-stellar/protostellar overlap, whereas in the outer Galaxy only a small fraction of pre-stellar clumps is found above this threshold. As seen by Zhang et al (2020), quiescent massive clumps associated with H regions can reach bol / > 10 / because of significant external heating, suggesting a more advanced evolutionary state than is the case. The higher density of H regions in the inner Galaxy compared to the outer Galaxy (Anderson et al 2014) and, in general, the stronger interstellar radiation field (e.g., Mathis et al 1983) can create the higher degree of overlap in the inner Galaxy.…”
Section: Luminosity-mass Ratiomentioning
confidence: 90%
See 1 more Smart Citation
“…15 shows that in the inner Galaxy this threshold falls well inside the region of the pre-stellar/protostellar overlap, whereas in the outer Galaxy only a small fraction of pre-stellar clumps is found above this threshold. As seen by Zhang et al (2020), quiescent massive clumps associated with H regions can reach bol / > 10 / because of significant external heating, suggesting a more advanced evolutionary state than is the case. The higher density of H regions in the inner Galaxy compared to the outer Galaxy (Anderson et al 2014) and, in general, the stronger interstellar radiation field (e.g., Mathis et al 1983) can create the higher degree of overlap in the inner Galaxy.…”
Section: Luminosity-mass Ratiomentioning
confidence: 90%
“…This scatter corresponds to the relatively wide range of temperatures found (Section 4.2), which depends, in turn, on different levels of external irradiation (Section 4.6) combined with the absence of a central energy source. For example, recently Zhang et al (2020), focusing on massive starless clumps, showed that those associated with an H region generally exhibit larger bol / values, more typical of protostellar sources.…”
Section: Luminosity Vs Massmentioning
confidence: 99%
“…This scatter corresponds to the relatively wide range of temperatures found (Section 4.2), which depends, in turn, on different levels of external irradiation (Section 4.6) combined with the absence of a central energy source. For example, recently Zhang et al (2020), focusing on massive starless clumps, showed that those associated with an H region generally exhibit larger 𝐿 bol /𝑀 values, more typical of protostellar sources.…”
Section: Luminosity Vs Massmentioning
confidence: 99%
“…A unified T dust for all cores embedded in one HMSC, which normally comes from single-dish clump-scale observations, is not solid due to T dust gradients of the clump and different evolutionary stages of the cores. Dust temperature is expected to decline towards the center of starless clump (Guzmán et al 2015;Svoboda et al 2020;Zhang et al 2020). The temperature could drop to 10 K for the starless center (Lin et al 2020).…”
Section: Core Extraction and Physical Propertiesmentioning
confidence: 99%
“…Previous studies showed that at least 30% of HMSF in the Galaxy are located at the edges of the H ii regions (Deharveng et al 2010;Kendrew et al 2016;Palmeirim et al 2017). In our first paper (hereafter Paper I, Zhang et al 2020), we investigated the feedback of H ii regions on candidate HMSCs that are quiet from ∼ 1 µm to 70 µm and without any star-formation signposts (Yuan et al 2017). Higher resolution interferometric observations show that many of these candidate HMSCs are not absolutely starless because low-to intermediate-mass protostellar objects usually exist there (Feng et al 2016;Traficante et al 2017;Contreras et al 2018;Sanhueza et al 2019;Svoboda et al 2019;Pillai et al 2019;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%